Фінансове забезпечення конфесії адвентистів сьомого дня у період її становлення в Україні (кінець ХІХ – початок ХХ ст.) - Сітарчук, Р.А. (Інститут історії України НАН України, 2009)
В статье рассказывается о финансовой практике адвентистов седьмого дня в украинских землях в составе Российской империи в период формирования их организации. Она являлась одним из определяющих факторов во внутренней конфессиональной деятельности церкви. In the article told about financial practice of Adventists of seventh day in Ukrainian earths in composition the Russian empire in the period of forming of their organization. It was one of determinatives in internal confession activity of church.